The Impact of Corporate Governance Practices on Firm-Level Innovations and Their Market Value : Empirical Evidence from India - Thomas, Asha Elizabeth; Bhaumik, Amiya; Aruja, Jean Mary (Indian Journal of Finance, 2023)
Purpose : In this study, empirical data from non-financial companies listed on Indian stock markets was used to assess the impact of firm-level innovation on the market value of Indian enterprises. This study also looked into how corporate governance practices affect the growth of an innovative ecosystem in the Indian market. Methodology : We evaluated data of the 77 non-financial companies listed on the BSE 200 index using the fixed effect panel data regression technique. The experimental phase lasted six years, from 2016 to 2021. The market value of the company was determined using the price-to-book ratio. The moderating influence of corporate governance characteristics on market value was measured using three factors: board independence, promoter stake, and CEO duality. Measurement of R&D spending relative to total sales was used as a stand-in for innovation level in the selected companies. Findings : The results showed a substantial correlation between firm-level innovation and the market valuation of the research’s selected enterprises. The empirical evidence supported the hypothesis that corporate governance mechanisms can catalyze the innovation ecosystem in the selected firms. Practical Implications : This study clearly demonstrated that while some corporate governance elements augment the level of innovation in businesses, a small number of other variables can impair the innovation ecosystem in those businesses. Originality/Value : This study expanded on earlier research by examining how corporate governance practices affect firm-level innovations and their market value.